Kirk-Othmer Encyclopedia of Chemical Technology 2004
DOI: 10.1002/0471238961.herbduke.a01
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides, Biotechnology

Abstract: Biotechnology can be used to enhance the management weeds in several ways. Crops have been made resistant to herbicides by inserting transgenes that impart herbicide resistance into the plant genome. Glyphosate‐, glufosinate‐, and bromoxynil‐resistant crops are commercialized in North America. This technology has been highly successful, transforming weed management in several major crops. Selection for mutations that impart herbicide resistance to crops has also been successfully used to generate herbicide‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Biotechnology is the technological application in biology, primarily involving the transfer of genetic material containing a specific trait from one crop/organism to another in order to improve crop productivity and resistance to various biotic and abiotic stresses. Many on-farm and small-plot research studies demonstrated that biotechnological intervention could improve crop yield and nutrient quality [4], and weed management [5] without affecting the ecosystem and environment. Engineered crops like glyphosate-resistant crops make weed control simple and more efficient [6].…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnology is the technological application in biology, primarily involving the transfer of genetic material containing a specific trait from one crop/organism to another in order to improve crop productivity and resistance to various biotic and abiotic stresses. Many on-farm and small-plot research studies demonstrated that biotechnological intervention could improve crop yield and nutrient quality [4], and weed management [5] without affecting the ecosystem and environment. Engineered crops like glyphosate-resistant crops make weed control simple and more efficient [6].…”
Section: Introductionmentioning
confidence: 99%